Tumour Necrosis Factor Inhibitors and Infection: What Is there to Know for Infectious Diseases Physicians?. Issue 4 (1st August 2006) - Johnston, BL; Conly, JM
Abstract : At this year's meeting of Digestive Disease Week in Los Angeles, California, it was noted that antitumour necrosis factor (anti-TNF) inhibitors showed further evidence of efficacy in Crohn's disease (1). TNF antagonists have been used increasingly in the treatment of a number of other inflammatory diseases, especially rheumatoid arthritis (RA), where they have revolutionized treatment (2). At the same time, their use has been associated with an increased risk of serious infections (3). As more patients are treated with these agents, it is inevitable that infectious diseases physicians will see a variety of infections, both common and uncommon, requiring familiarity with this new class of drugs and their infectious complications.